An Efficient Bioorthogonal Strategy Using CuAAC Click Chemistry for Radiofluorinations of SNEW Peptides and the Role of Copper Depletion1. Issue 6 (4th April 2013) - Pretze, Marc; Kuchar, Manuela; Bergmann, Ralf; Steinbach, Jörg; Pietzsch, Jens; Mamat, Constantin
Abstract: The EphB2 receptor is known to be overexpressed in various types of cancer and is therefore a promising target for tumor cell imaging by positron emission tomography (PET). In this regard, imaging could facilitate the early detection of EphB2‐overexpressing tumors, monitoring responses to therapy directed toward EphB2, and thus improvement in patient outcomes. We report the synthesis and evaluation of several fluorine‐18‐labeled peptides containing the SNEW amino acid motif, with high affinity for the EphB2 receptor, for their potential as radiotracers in the non‐invasive imaging of cancer using PET. For the purposes of radiofluorination, EphB2‐antagonistic SNEW peptides were varied at the C terminus by the introduction ofL ‐cysteine, and further by alkyne‐ or azide‐modified amino acids. In addition, two novel bifunctional and bioorthogonal labeling building blocks [ 18 F]AFP and [ 18 F]BFP were applied, and their capacity to introduce fluorine‐18 was compared with that of the established building block [ 18 F]FBAM. Copper‐assisted Huisgen 1, 3‐dipolar cycloaddition, which belongs to the set of bioorthogonal click chemistry reactions, was used to introduce both novel building blocks into azide‐ or alkyne‐modified SNEW peptides under mild conditions. Finally, the depletion of copper immediately after radiolabeling is a highly important step of this novel methodology. Abstract : Introduction and removal: Fluorine‐18‐labeled radiotracers based on SNEW peptides with high affinity for the EphB2 receptor were developed through a bioorthogonal CuAAC approach. The copper species must be removed to circumvent loss in biological activity. Radiopharmacological characterizations of a selected 18 F‐labeled peptide were initially carried out in vitro and then in vivo using Wistar rats.